2022
DOI: 10.3390/s22031171
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability of Kinematic and Temporal Outcome Measures for Clinical Gait and Stair Walking Tests, Based on Wearable Inertial Sensors

Abstract: It is important to assess gait function in neurological disorders. A common outcome measure from clinical walking tests is average speed, which is reliable but does not capture important kinematical and temporal aspects of gait function. An extended gait analysis must be time efficient and reliable to be included in the clinical routine. The aim of this study was to add an inertial sensor system to a gait test battery and analyze the test-retest reliability of kinematic and temporal outcome measures. Measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…A practical problem is that most hospitals have magnetic materials in walls, floors, and surrounding equipment that give magnetic disturbances. In that case, magnetometers can be excluded, and a simplified calibration procedure needs to be utilized, assuming that all joint angles are zero during the standardized starting position [ 46 ]. In this case, we recommend RoM values to avoid systematic errors related to BPBI patients having difficulties holding their arms in such a straight, standardized position.…”
Section: Discussionmentioning
confidence: 99%
“…A practical problem is that most hospitals have magnetic materials in walls, floors, and surrounding equipment that give magnetic disturbances. In that case, magnetometers can be excluded, and a simplified calibration procedure needs to be utilized, assuming that all joint angles are zero during the standardized starting position [ 46 ]. In this case, we recommend RoM values to avoid systematic errors related to BPBI patients having difficulties holding their arms in such a straight, standardized position.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, changes in general gait patterns could be monitored, rather than absolute segment angles. Future studies would also be needed to assess the test-retest reliability between days of this Bluetooth IS system; however, we expect this system would be reliable as previous studies have found moderate to excellent test-retest reliability of IS systems 35,36) , one of which was Bluetooth connected 35) .…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional (3D) optoelectronic systems are considered the Gold Standard in the analysis of movement, surpassing clinical observation [ 20 , 21 ]. Despite this, due to its relatively high cost and the time and space required to develop an analysis using these systems [ 22 ], in addition to the difficulty of analyzing certain planes in 3D, the technological progress has enabled the development of more affordable, accessible, and feasible devices [ 23 ].…”
Section: Introductionmentioning
confidence: 99%